2015
DOI: 10.18267/j.efaj.147
|View full text |Cite
|
Sign up to set email alerts
|

Deductibility of Provisions under the CCCTB Proposal and Its Effects on Companies: The Case of Poland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The above described results extend those obtained in Leszczyłowska [2015]. Analyzing the distribution of the changes in corporate income tax, she observed that the reduction in the multi-period tax due induced by the deductibility of provisions ranges from 1% for the median company in the group of firms with positive cash flow to 2% for the median company in the group of firms with negative cash flow.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The above described results extend those obtained in Leszczyłowska [2015]. Analyzing the distribution of the changes in corporate income tax, she observed that the reduction in the multi-period tax due induced by the deductibility of provisions ranges from 1% for the median company in the group of firms with positive cash flow to 2% for the median company in the group of firms with negative cash flow.…”
Section: Resultssupporting
confidence: 81%
“…Additionally, they simulated the consequences in case the common tax base is optional as well as the effects of that concept on compliance costs. Leszczyłowska [2015] concentrated on the tax advantage caused by the accelerated deduction of provisions under the CCTB proposal from the perspective of Polish taxpayers. She examined empirically the scale and the distributional effects of these tax advantages.…”
Section: Introductionmentioning
confidence: 99%